Percy Bysshe Shelley : the critical heritage - Barcus, James E. (James Edgar) (Critical heritage series., 1975)
The Critical Heritage gathers together a large body of critical sources on major figures in literature. Each volume presents contemporary responses to a writer's work, enabling student and researcher to read the material themselves.